Answer:
[tex]x=-3.05[/tex]
Step-by-step explanation:
[tex]\frac{-2}{5(x+3)} =8[/tex]
1. The first step is to distribute the 5 to the (x+3) which changes [tex]\frac{-2}{5(x+3)} =8\\[/tex] to [tex]\frac{-2}{5x+15} =8[/tex].
2. The second step is to get x out of the denominator, so in order to do that, you have to multiply 5x+15 to both sides of the equation. Doing that cancels out the 5x+15 on the left side of the equation and changes the right side of the equation so it looks like this:
[tex]-2=8(5x+15)[/tex]
3. The third step is to distribute the 8 to (5x+15) which changes the equation to look like:
[tex]-2=40x+120[/tex]
4. The fourth step is to get x by itself so you want to get 120 on the left side of the equation so it looks like this:
[tex]-2=40x+120[/tex]
-120 -120
[tex]-122=40x[/tex]
5. Finally to solve for x we have to divide by 40 to each side because right now 40 is being multiplied to x, so the answer will look like this:
[tex]\frac{-122}{40}=\frac{40x}{40}[/tex]
[tex]x=-3.05[/tex]